ARTEMISIA ANNUA AS A SOURCE OF BIOLOGICALLY ACTIVE SUBSTANCES OF PHENOLIC NATURE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The composition of phenolic compounds from samples of the above-ground masscollected during the flowering period and the lines of transformed roots of Artemisia annua L.was analyzed. The efficiency of bioactive compounds extraction using ultrasonic and microwavetreatment at different duration and temperature of the process was evaluated. The chemicalcomposition, in particular, the content of caffeylquinic acids and their derivatives as the mainactive substances in the extracts of wormwood were determined by liquid chromatography withmass-selective and diode-array detectors.
Keywords: Artemisia annua L., “hairy” roots, hydroxycinnamic acids, extraction, ultrasonic treatment.